ANALISIS KEMAMPUAN REPRESENTASI MATEMATIS SISWA DITINJAU DARI KECEMASAN MATEMATIKA [ANALYSIS OF STUDENTS' MATHEMATICAL REPRESENTATION ABILITY IN TERMS OF MATH ANXIETY] - Andriani, Nur Lisa; Fauziyah, Nur (Universitas Pelita Harapan, 2024)
The purpose of this research is to describe the profile of students' mathematical representation ability in terms of math anxiety. This research method is descriptive qualitative method. The research was conducted at SMAN 1 Manyar with the research subjects being 3 class X students, consisting of students with low, medium, and high levels of math anxiety. There are two instruments in this study, namely a math anxiety questionnaire and mathematical representation ability test questions. Data analysis techniques used in this study consist of data reduction, data presentation, and conclusion drawing. The results of the research data showed the profile of mathematical representation ability (1) subjects with “low” math anxiety level had good visual representation ability, but still lacking in symbolic and verbal representation, (2) Subjects with “medium” math anxiety level had quite good visual mathematical representation ability, but still lacking in symbolic and verbal representation (3) subjects with “high” math anxiety level did not fulfill all of the three indicators of mathematical representation ability.BAHASA INDONESIA ABSTRACT: Tujuan penelitian ini adalah mendeskripsikan profil kemampuan representasi matematis siswa yang ditinjau dari kecemasan matematika. Metode penelitian ini adalah metode kualitatif deskriptif. Penelitian dilakukan di SMAN 1 Manyar dengan subjek penelitian 3 siswa kelas X, yang terdiri dari siswa dengan tingkat kecemasan matematika rendah, sedang, dan tinggi. Terdapat dua instrumen pada penelitian ini yaitu angket kecemasan matematika dan soal tes kemampuan representasi matematis. Teknik analisis data yang digunakan pada penelitian ini terdiri dari reduksi data, penyajian data, dan penarikan kesimpulan. Hasil perolehan data penelitian menunjukkan profil kemampuan representasi matematis (1) subjek dengan tingkat kecemasan matematika “rendah” memiliki kemampuan representasi visual yang baik, namun masih kurang dalam representasi simbolik dan verbal, (2) Subjek dengan tingkat kecemasan matematika “sedang” memiliki kemampuan representasi matematis visual yang cukup baik, namun masih kurang dalam representasi simbolik dan verbal (3) subjek dengan tingkat kecemasan matematika “tinggi” tidak memenuhi semua dari tiga indikator kemampuan representasi matematis.